Comparison of Two Versions of the Hospital Anxiety and Depression Scale in Assessing Depression in a Neurologic Setting. Issue 4 (December 2017) - Patel, Viral P.; Feinstein, Anthony
Abstract : Background: The Hospital Anxiety and Depression Scale–Depression Subscale (HADS-D) is widely used to assess depression in people with multiple sclerosis (MS). Developed specifically for use in a medical setting, the scale has one item, "I feel as if I am slowed down, " that might represent a significant somatic confounder, possibly biasing the assessment. Objective: We sought to determine whether inclusion or exclusion of the "slowed down" item in the HADS-D affects the detection of depression and the scale's associations with impaired cognition, fatigue, and employment status. Methods: A sample of 193 people with confirmed MS completed the HADS. To identify depressed participants, we used previously established cutoff scores for the HADS-D with (≥8) and without (≥6) the "slowed down" item. Linear and logistic regression models were used to determine predictors of cognition and employment status. Results: The HADS-D with and without the "slowed down" item detected similar rates of depression: 30.6% and 31.6%, respectively. Both versions of the HADS-D predicted processing speed and executive functioning, but not memory. Neither version predicted employment status. Conclusions: The HADS-D is an easy-to-use and clinically relevant self-report psychometric scale for detecting depression in MS. Removing the "slowed down" item from the HADS-D does not influence its internal consistency, and both versions have similar associations with clinical outcomes.